Je v referendumskem sporu ustavnopravno kaj novega - Sovdat, Jadranka (Podjetje in delo, 2018)
The right to vote in a referendum is protected in a special judicial procedure referred to as the referendum dispute. A judge is the ulimate guardian of the lawfulness of a referendum. The result thereof should be an accurate reflection on the reeely expressed will of the voters. The article presents the views of the Slovene constitutional law theory on the referendum dispute and the positions of the Constitutional Court adopted in Decision U-I-191/17. By comparing these views and positions, it formulates new positions as to the referendum dispute and provides advice regarding the future legislative regulation thereof.
Keywords: pravica glasovanja na referendumu; referendumski spor; ustavno sodišče; zakonodajni referendum